Influence of smoking status on acute biomarker responses to successive days of arduous military training. Issue 1 (19th July 2020) - Siddall, A G; Stokes, K A; Thompson, D; Izard, R; Greeves, J; Bilzon, J L J
Abstract : Introduction: Habitual smoking is highly prevalent in military populations despite its association with poorer training outcomes. Smoking imposes challenges on the immune and endocrine systems which could alter how smokers acutely respond to, and recover from, intensive exercise particularly over multiple days of training. Methods: Over a two-day period, 35 male British Army recruits (age 22±3 years; mass 76.9±8.0 kg; height 1.78±0.06 m; 15 smokers) completed a 16.1 km loaded march (19.1 kg additional mass) on the first morning and a best-effort 3.2 km 'log race' (carrying a 60 kg log between six and eight people) on the subsequent morning. Blood samples were obtained on waking and immediately postexercise on both days and analysed for C reactive protein (CRP), interleukin 6 (IL-6), testosterone to cortisol ratio and insulin-like growth factor 1 (IGF-1). Results: Independent of smoking group, the exercise bouts on both days evoked significant increases in IL-6 (p<0.001) and decreases in testosterone to cortisol ratio (p<0.05). CRP concentrations on day 2 were significantly higher than both time points on day 1 (p<0.001), and a 9% decline in IGF-1 occurred over the two-day period, but was not significant (p=0.063). No significant differences were observed between smokers and non-smokers (p>0.05). Conclusions: Military-specific tasks elicited inflammatory and endocrine responses, with systemic CRP and IGF-1 indicating that the physiological stress generated during the first training day was still evident on the second day. Despite the well-established impacts of smoking on resting levels of the markers examined, responses to two days of arduous military-specific training did not differ by smoking status.